Peran Orang Tua dalam Membentuk Karakter Anak Usia Dini di Desa Sipaho Kecamatan Halongonan Kabupaten Padang Lawas Utara - Siregar, Erma Sri Yuliani; Basri, Muhammad; Al Farabi, Mohammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to: (1) identify the role of parents in shaping a child's character (2) describe the exemplary behavior of parents in shaping a child's character (3) describe the habits of parents in shaping a child's character (4) describe the supporting and inhibiting factors of parents in shaping a child's character. This type of research uses a qualitative method. In collecting data, the researcher uses observation, interviews, and documentation methods. Based on the research results, parents play a significant role in the process of shaping a child's character. They focus on the child's conditions, understand their nature, and provide good examples to the child. The exemplary behavior and habits of parents in shaping a child's character include introducing God's commands to the child through worship, mutual respect, and courtesy. Children are also accustomed to applying these in their daily lives. Supporting factors in shaping a child's character include a good family and community environment, as well as support from the family. Meanwhile, inhibiting factors include excessive television and smartphone use, children playing too much, parental busyness, and a less favorable peer environment. The results of this research are expected to help parents understand their responsibilities and obligations to their children, as well as to prepare good education from an early age to shape the character and behavior of the child for their future development.